Germany's successfully developing industry for electric power assisted cycles. A multi-theoretical case study. - Wilbrand, Hanna (My University, 2016)
This thesis analyzes the development and influencing 'success-factors' of the German industry for electric power assisted cycles (EPACs). Earlier theoretical and case study research on industry development in economic geography highlight the importance of considering industrial peculiarities regarding structure, innovation, regulation, and institutions for empirical analysis. Against this background, this multi-theoretical case study is fruitfully guided by the empirical application of three theoretical frameworks: Michael Porter's approach of the diamond, emphasizing industrial interrelations; Benkt-Åke Lundvall's approach of National Systems of Innovation, focusing on learning, innovation, and R&D; and J. Roger Hollingsworth's and Robert Boyer's approach of Social Systems of Production, considering national idiosyncratic regulation and social constitutions. Through qualitative and quantitative verbal descriptions, the subsequent application of these frameworks, retraces the successful industry development and reflects upon the framework's suitability for industrial analysis. Each theoretical framework points to the existence of a particular set of different influencing 'success-factors' that have shaped the successful development. Regardless of the 'success-factors' coupled to a theoretical framework, all factors were closely intertwined and influenced the industrial formation during different development stages. These include: distinct national structure of related and supporting industries, sophisticated customers, 'green' mobility anchored in daily life, SME-structure and industry's size, trust in established enterprises, professionalization dynamics, informal horizontal and vertical knowledge accumulation, imitation and recombination practices, 'low' product complexity, (in-house) R&D in traditional industries, social values, industry associations, community and low hierarchy, product's quality and market dynamics. These 'success-factors' appear to work on different spatial and organizational scales and can be aggregated to societal and functional types. Each 'success-factor' structures the industrial formation and has enabling, guiding, or facilitating functions.
Keywords: Individualverkehr; Fahrrad; Industrie; Wirtschaftszweig; Wirtschaftsgeographie; Innovation; Motorisierung; Elektroantrieb; E-Bike; Pedelec; Elektromobilität